Implementation of BSI Mobile Application on Customer Efficiency in Paying Zakat, Infaq, and Waqaf - Lailiyatul Barokah; Nur Anim Jauhariyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This Study aiming for analyze implementation application BSI mobile towards efficiency Customer in payment charity, charity, And endowment (ZISWAF) in BSI KCP Rogojampi Banyuwangi. Research This using the method quantitative with approach descriptive. Data was collected through a questionnaire distributed to customers who use the BSI application Mobile For payment ZISWAF. Respondents study amount to 100 Customer the selected one-use technique purposive sampling. Analysis data done with using techniques statistics descriptive for measure level efficiency Which covering convenience, speed, and accuracy transaction. Results study show that 85% Customer feel application BSI Mobile make it easier transaction ZISWAF, 75% feel that time transaction reduced in significant, and 90% feel report transaction Which accepted accurate and appropriate time. Besides That, application This Also play a role important in increase literacy finance digital among customers. However, constraint in the form of lack of understanding technology in customer circles carry on age become challenge in implementation Which wider. Conclusion from research This is that implementation application BSI Mobile in a way significant increase efficiency payment ZISWAF in BSI KCP Rogojampi Banyuwangi. Results study This can become reference for banking sharia other in optimize service digital For transaction ZISWAF.